2014
DOI: 10.9734/bmrj/2014/10203
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis E Virus among Domestic Animals in Plateau State–Nigeria

Abstract: Aim: This study was undertaken to determine the epidemiology, seroprevalence and associated risk factors, of Hepatitis E virus (HEV) among domestic animals. Study Design: Cross sectional epidemiological survey. Place and Duration: The study was carried out in three geographical zones of Plateau State, over a six month period from July to December, 2012. Methodology: A total of 166 animal subjects were recruited into the study. The animals studied were made up of pigs (67), goats (43), sheep (19) and cattle (37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
3
11
2
Order By: Relevance
“…We noted anti-HEV IgM and IgG seropositivity of 21.0% and 17.7% respectively which is higher than reports from Nigeria and Mexico and lower than reports from Madagascar and Scotland [2,10,14,15]. These differences could be explained, at least partly, by the different pig husbandry systems, the routine management and hygiene practices applied on these pig farms and environmental conditions that characterize various areas [16]. This difference may also be associated with the different HEV diagnostic methods used in these different studies.…”
Section: Discussioncontrasting
confidence: 65%
“…We noted anti-HEV IgM and IgG seropositivity of 21.0% and 17.7% respectively which is higher than reports from Nigeria and Mexico and lower than reports from Madagascar and Scotland [2,10,14,15]. These differences could be explained, at least partly, by the different pig husbandry systems, the routine management and hygiene practices applied on these pig farms and environmental conditions that characterize various areas [16]. This difference may also be associated with the different HEV diagnostic methods used in these different studies.…”
Section: Discussioncontrasting
confidence: 65%
“…Thus, the prevalence of HEV antibodies in pigs found in Zaria as determined by our study was 24.4%. This prevalence is comparatively lower than what was reported in previous studies carried out in Nigeria (32.8%) (Junaid et al, 2014), Thailand (30.7%) , United States of America (34.5%) (Withers et al, 2002), Taiwan (37.1%) (Hsieh et al, 1999), Japan (93%) , Spain (98%) (Seminati et al, 2008), Laos (46%) (Blacksell et al, 2007) and Brasil (81%) (Dos Santos et al, 2009). …”
Section: Resultscontrasting
confidence: 57%
“…The discrepancies in prevalence rates across various geographical areas have been attributed to socioeconomic, cultural, hygienic and climatic conditions that characterize various areas (Junaid et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the infection rate of HEV3 was 28.7% and this percentage corroborates with results of several studies done in China such as Geng et al (2014) and Zhang et al (2010) who found 28.2 and 24% infection rate, respectively and lower than that reported in United States 16% (Sanford et al, 2013) and in Egypt 9.4% (El-Tras et al, 2013). A higher prevalence of 37.2% has been recorded in Plateau State, Nigeria (Junaid et al, 2014).…”
Section: Discussionsupporting
confidence: 91%